Teaching English Vocabulary By Using Games To The Fourth Year Students Of SD Negeri 2 Bogor Cawas Klaten In 2011-2012 Academic Year - Yuwanita, Riski (2012)
The aim of this research is to describe the implementation of teaching vocabulary by using games at fourth year students of SD Negeri 2 Bogor Cawas Klaten, the responses of the students, the effectiveness of games, and the strength also the weakness of teaching vocabulary by using games at fourth year students of SD Negeri 2 Bogor Cawas Klaten. The writer uses descriptive research. The writer collects the data of this research from the observation and interview with the English teacher and the students. The result of this research shows: (1) the implementation of teaching vocabulary by using games are (a) teaching vocabulary by using games makes the students be interested in the lesson and easier to absorb their new English vocabulary so they do not learn English vocabulary too hard, (b) the reasons of the teacher choosing games as techniques for teaching vocabulary because children are still like playing also making interaction with others and when the teacher teaches in the serious way the students will be bored, (c) the teacher uses some games which combined with card, picture, song, and props, (d) the technique for teaching vocabulary by using games is the teacher divides class into several groups in order to make the games more attractive ; (2) the fourth year students are enthusiastic to learn English vocabulary by using games. They enjoyed the material, feel more comfortable and not be bored when learn English words in the classroom; (3) games are effective to introduce some new English vocabularies to the fourth year students of SD Negeri 2 Bogor cawas Klaten. Games can get the student's attention. With games, the fourth year students will be able to experience their study and get meaningful learning; (4) the strength and the weakness of teaching vocabulary by using games is as follows: (a) the strength of teaching English vocabulary using games are games makes the students enjoy their study, they will be easier to absorb their materials, games will motivate the students to learn English vocabulary, and the closeness between others will be formed; (b) the weakness of teaching vocabulary by using games are teacher needs more time to handle the class because the students more enthusiastic allowed the games and the students are addicted to play games.